2019
DOI: 10.6000/1929-7092.2019.08.22
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Relationship between Exports, Imports and Economic Growth in Palestine

Abstract: The relationship between exports, imports and economic growth is investigated for the Palestinian economy over the period 2000-2018, using quarterly data. To do so, cointegration test using Johansen's approach as well as vector error correction technique are used. Findings confirm the presence of long-run equilibrium relationship between exports, imports and output growth. Results also support the existence of bidirectional long-run causality between exports, imports and output growth. As for the short-run cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…Moreover, the author has found a bidirectional causal link between development and exports, with causality from foreign direct investment to economic growth, and with causality also running from foreign direct investment to exports. The results of the study by Fannoun and Hassouneh (2019) confirmed the existence of a link between imports, exports, and output in Palestine during the period 2000-2018. The authors noticed that policymakers should focus on international trade when it comes to being able to stimulate development.…”
Section: Findings Of Recent Investigationssupporting
confidence: 54%
See 1 more Smart Citation
“…Moreover, the author has found a bidirectional causal link between development and exports, with causality from foreign direct investment to economic growth, and with causality also running from foreign direct investment to exports. The results of the study by Fannoun and Hassouneh (2019) confirmed the existence of a link between imports, exports, and output in Palestine during the period 2000-2018. The authors noticed that policymakers should focus on international trade when it comes to being able to stimulate development.…”
Section: Findings Of Recent Investigationssupporting
confidence: 54%
“…From the literature review mentioned above, the inter-linkage between exports and economic development has been and still are a subject of intensive debate amongst researchers and policymakers, with inconclusive outcomes being reached along the way. The findings of investigations have varied across the countries involved (Trošt & Bojnec, 2015;Ee, 2016;Dinc & Gokmen, 2019;Sultanuzzaman et al, 2019;Fannoun & Hassouneh, 2019;Mensah & Okyere, 2020). This research has shown that evidence exists in regard to a correlation between exports and economic development.…”
Section: Discussionmentioning
confidence: 97%
“…Bakari and Krit (2017) discovered one-way causation among imports and economic growth and could not have any causal relation between export and GDP. Fannoun and Islam (2019) exposed the long-run dual causality among export, import, and economic growth in Palestine. The short-run outcomes supported export-led import and import-led export hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…Exports are various kinds of goods and services that have been produced domestically and sold abroad (Puspitasari, 2014). Exports are one of the foreign sources that are used as a reduction in income and can create labor and increase income (Fannoun, 2019). Various economists have stated that increasing exports can increase economic growth because exports are an element of GDP (Md.…”
Section: Exports and Gdpmentioning
confidence: 99%